UTILIZATION OF E-WASTE IN ROAD POTHOLES - Mr. Vardhaman M. Lunawat (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Electronic waste is serious pollution problems to the humans and the environment. The disposal of E-waste is becoming a challenging problem. For solving the disposal of large amount of E-waste material, reuse of E-waste in road potholes as filler material is considered as the most feasible application. In India, bitumen pavements are commonly used for highways. Due to the increasing traffic intensity, distress such as rutting and cracking of pavements are very common in Indian roads. Under varying seasonal temperature, flexible pavements tend to become soft in summer and brittle in winter. Due to increase in cost of boulders (aggregate), labors and bitumen it has forced the civil engineers to find out suitable alternatives to it. E-waste is used as one such alternative as road filling material. Owing to scarcity of natural materials as well as considering the economic factor in road patch work so the E-waste as an alternative was attempted in pothole with the mixture of waste foundry sand, cement, course aggregate, chemicals. The work was conducted on practical pothole. Finally the mechanical properties and durability of these mixture specimens were obtained. The test results showed that a significant improvement in compressive strength, weather resistance, impact resistance and less water absorption was achieved in the E-waste road pothole filler mixture and hence can be used effectively in pothole filling. The reuse of E-waste results in waste reduction and resources conservation as well as safe disposal of E-waste.